Measurement and SAFT modelling of hydrogen bonding in binary alcohol and ester systems - Erasmus, Melissa (Stellenbosch : Stellenbosch University, 2025)
Erasmus, M. 2025. Measurement and SAFT modelling of hydrogen bonding in binary alcohol and ester systems. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/daab1805-72eb-4d77-87a8-be0c02708b11